A marker detection method using hysteresis thresholding for human posture tracking: A head tracking system - Dirican, Ahmet Cengizhan (Association for Computing Machinery, 2014)
This paper presents an easy to implement and fast marker detection method suitable for real-time marker-based human posture tracking. The method works on a color segmentation algorithm based on hysteresis thresholding conducted on meaningful pixels in an image. After the segmentation algorithm is described, the experimental results for an artificial scene are given. Then, the applicability of the method is examined by means of a postural tracking application. The change in elbow angle between upper arm and forearm of a person is tracked during continuous flexion and extension movements with 21.5 Hz frequency for 640× 480 resolution. The paper finally introduces the head tracking system developed using the proposed marker detection method. © 2021 Elsevier B.V., All rights reserved.
7th ACM International Conference on Pervasive Technologies Related to Assistive Environments, PETRA 2014 -- Rhodes -- 113522
Keywords: Body motion; Head; Hysteresis thresholding; Marker-based; Motion tracking; Posture; Segmentation